Utilization of Animated Films for Learning Everyday Vocabulary in Improving Arabic Speaking Skills - Ahsanu Ibadillah, Faris; Alif Cahya Setiyadi; Nofiem Taufiqul Akbar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
In today's era of technological development, electronic-based media is a highly desirable tool, especially for children. The majority of technology contains entertainment and games that often interfere with children's interest in learning. This requires teachers to develop more creative and effective learning strategies to achieve learning objectives. This study aims to describe the use of digital media-based learning methods in the form of animated videos in learning language vocabulary, considering that children generally love animated movies. The usual lecture method is considered boring by students, thus reducing interest in learning. This research uses observation and interview methods to analyze the effectiveness of Arabic vocabulary learning through animated videos. The results show that this method is very instrumental in increasing children's interest and participation in the learning process. Children are more interested in learning new Arabic vocabulary through animated media, which they consider more fun than traditional methods. In addition, this method also strengthens students' memory of the Arabic vocabulary learned. Based on these findings, the use of animated videos in vocabulary learning proved to be an effective solution in increasing students' interest in learning and understanding of the material taught.